A fuzzy decision support system for personal loan application / Muhammad Mustaqim Md Said - Md Said, Muhammad Mustaqim (2017)
Due to the competition among financial institution, like banks and investment firms, they have been introduce a lot of personal loan scheme to the customer. In business world, is good when lot of choices provided for customer to choose. However, it will make customer hard to identify which personal loan scheme suitable for applicant based on customer information. Every personal loan scheme has different term and condition. Apparently, the committee approval system are very slow and the quality of decision not good enough. In this institution heavily rely on technology to manipulate daily operation and support business. Decision support system is interactive computer system that assists people in decision making process. Fuzzy logic can be adapted in decision support system and it can produce reliable and flexible result for the system. This paper discuss the implementation of decision support system for personal loan applicant using fuzzy logic in banking institution. This algorithm being implemented in order to help customer in identifying the suitable personal loan scheme. The evaluation have been done with loan expert in testing different applicant’s information. The result produce 76.67% accuracy on approving personal loan and reliable in recommending the correct personal loan scheme for applicant.